Population genetic structure, antibiotic resistance, capsule switching and evolution of invasive pneumococci before conjugate vaccination in Malawi. Issue 35 (16th August 2017) - Chaguza, Chrispin; Cornick, Jennifer E.; Andam, Cheryl P.; Gladstone, Rebecca A.; Alaerts, Maaike; Musicha, Patrick; Peno, Chikondi; Bar-Zeev, Naor; Kamng'ona, Arox W.; Kiran, Anmol M.; Msefula, Chisomo L.; McGee, Lesley; et al.
Highlights: High pneumococcal population diversity in terms of serotypes and sequence types (ST). Decline in IPD incidence pre-vaccination not associated with specific serotypes. High prevalence and antibiotic resistance rates in serotype 1 isolates. High levels of capsule (serotype) switching pre-vaccination. Surveillance remains crucial to understand pneumococcal epidemiology. Abstract: Introduction: Pneumococcal infections cause a high death toll in Sub Saharan Africa (SSA) but the recently rolled out pneumococcal conjugate vaccines (PCV) will reduce the disease burden. To better understand the population impact of these vaccines, comprehensive analysis of large collections of pneumococcal isolates sampled prior to vaccination is required. Here we present a population genomic study of the invasive pneumococcal isolates sampled before the implementation of PCV13 in Malawi. Materials and methods: We retrospectively sampled and whole genome sequenced 585 invasive isolates from 2004 to 2010. We determine the pneumococcal population genetic structure and assessed serotype prevalence, antibiotic resistance rates, and the occurrence of serotype switching. Results: Population structure analysis revealed 22 genetically distinct sequence clusters (SCs), which consisted of closely related isolates. Serotype 1 (ST217), a vaccine-associated serotype in clade SC2, showed highest prevalence (19.3%), and was associated with the highest MDR rate (81.9%) followed by serotype 12F, a non-vaccine serotype in clade SC10 with an MDR rate of 57.9%. Prevalence of serotypes was stable prior to vaccination although there was an increase in the PMEN19 clone, serotype 5 ST289, in clade SC1 in 2010 suggesting a potential undetected local outbreak. Coalescent analysis revealed recent emergence of the SCs and there was evidence of natural capsule switching in the absence of vaccine induced selection pressure. Furthermore, majority of the highly prevalent capsule-switched isolates were associated with acquisition of vaccine-targeted capsules. Conclusions: This study provides descriptions of capsule-switched serotypes and serotypes with potential to cause serotype replacement post-vaccination such as 12F. Continued surveillance is critical to monitor these serotypes and antibiotic resistance in order to design better infection prevention and control measures such as inclusion of emerging replacement serotypes in future conjugate vaccines.